Mode division multiplexing over 19‐cell hollow‐core photonic bandgap fibre by employing integrated mode multiplexer. Issue 17 (1st August 2014) - Chen, Haoshuo; van Uden, R.G.H.; Okonkwo, C.M.; Jung, Yongmin; Wheeler, N.V.; Fokoua, E.N.; Baddela, N.; Petrovich, M.N.; Poletti, F.; Richardson, D.J.; Raz, O.; de Waardt, H.; et al.
Abstract : A photonic integrated mode coupler based on silicon‐on‐insulator is employed for mode division multiplexing (MDM) over a 193 m 19‐cell hollow‐core photonic bandgap fibre (HC‐PBGF) with a −3 dB bandwidth >120 nm. Robust MDM transmissions using LP01 and LP11 modes, and two degenerate LP11 modes (LP11a and LP11b ) are both experimentally verified.